GREEN TIO2/ENR/PVC Nanocomposites with improved tensile strength for cable insulator / Nur Azrini Ramlee … [et al.] - Ramlee, Nur Azrini; Kamaluddin, Noor Azreena; Alias, Nurhashimah; Mohd Safaai, Nor Sharliza; Idris, Siti Noor Adeib (Research Innovation Business Unit, 2014)
Addition of inorganic fillers is seen as an emerging alternative method in polymer engineering area and it practice benefits to a contribution of advancement in material development. In cable insulator application, exposure to the conditions of high temperature, heat, oxygen and sunlight caused performance of conventional polyvinyl alcohol (PVC) cable insulator to become limited due to the acceleration of ageing. Application of titanium dioxide (TiO2) nanofillers has brought a new approach in cable insulator processing field since it has excellent characteristics including non-toxicity, long term stability and UV light discoloration resistance and they offer attractive potential for diversification and application of traditional polymeric materials. Green titanium dioxide, epoxidized natural rubber/polyvinyl chloride (TiO2/ENR/PVC) nanocomposites were prepared via direct melt-blending technique in which the approach is compatible with the current industrial process. The composites were then being exposed to the environmental friendly and sustainable electron beam irradiation prior to the polymer crosslinking. Result shows that the applied irradiation dose rate and TiO2 nanofillers loading have contributed to the overall tensile strength (Ts) performance of the green TiO2/ENR/PVC nanocomposites. In accordance to the specification for p¬¬vc insulation and electric cables (BS6746) tensile strength measurement, results have shown that at all level of irradiation dose rate from 0-200 kGy, Ts values of the TiO2/ENR/PVC nanocomposites at 6 wt % of TiO2 nanofillers loading are higher than the unmodified blends. Moreover, addition of 6 wt% of TiO2 nanofillers has shown the highest tensile strength with 6.85 MPa at 50 kGy of exposed dose rate. This result has contributed to 25.9%, which significantly higher than the unmodified blends. In comparison to the green TiO2/ENR/PVC nanocomposites with 6 wt% of TiO2 loadings, higher degree of crosslinking were obtained due to the presence of nanoparticles in the formation of crosslink in ENR/PVC blends matrix. Good distribution of TiO2 nanofillers was also observed using transmission electron microscope (TEM) at high magnification of 20000x and 40000x. This is apparently an evidence to support that the preparation of these green (TiO2/ENR/PVC) nanocomposites by melt blending technique has offered good dispersion of TiO2 in the ENR/PVC blends matrices. Based on all outcomes, it is well justify that the factors including preparation via melt blending, addition of TiO2 nanofillers at low loadings, and exposure to low dose rate of crosslinking were seemed feasible to the development of an economical, green and sustainable PVC cable insulator in future.